Localization of Transmitting Devices in Multipath Environment Using MUSIC And Neural Networks - Jaromir GAJEWSKI; Jerzy ŁOPATKA (Communications of International Proceedings, 2025)
This research examines the efficacy of the MUSIC algorithm in the context of electromagnetic wave propagation in urban environment. The Multiple Signal Classification (MUSIC) algorithm, known for its adaptability in direction-of-arrival estimation is analyzed for its efficacy in multipath propagation in urban areas, where reflections, diffractions and signal interactions with various obstacles may occur. The algorithm's practical applications for emitters localization in complex, multipath-dense situations are analyzed. The study contains insights into the algorithm's performance under various settings using simulated real-world scenarios. This research serves as proposal for the continued investigation of sophisticated localization methods in dynamic urban settings.
Keywords: multipath propagation; MUSIC algorithm; urban environments; localization